2022
DOI: 10.1111/fwb.13985
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the ecological impacts of alien aquatic macrophytes: A global meta‐analysis of effects on fish, macroinvertebrate and macrophyte assemblages

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 174 publications
(191 reference statements)
1
15
0
Order By: Relevance
“…89,90 Invasion of exotic macrophytes has a strong detrimental impact on the abundance and diversity of the resident macrophytes, with common species becoming more widespread and rare species becoming rarer. 4,89 A previous study showed invasion of A. philoxeroides significantly reduced the number of species and seedling density in the soil seed bank of the reed community. 91 However, we did not discover any obvious effects of invasive plants on the plant biomass, ramet number, and RGR of the native species, probably because the two species selected for this study had high environmental adaptability, 20,40 resulting in a relatively weak influence of invasive plants on their morphological traits.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…89,90 Invasion of exotic macrophytes has a strong detrimental impact on the abundance and diversity of the resident macrophytes, with common species becoming more widespread and rare species becoming rarer. 4,89 A previous study showed invasion of A. philoxeroides significantly reduced the number of species and seedling density in the soil seed bank of the reed community. 91 However, we did not discover any obvious effects of invasive plants on the plant biomass, ramet number, and RGR of the native species, probably because the two species selected for this study had high environmental adaptability, 20,40 resulting in a relatively weak influence of invasive plants on their morphological traits.…”
Section: Discussionmentioning
confidence: 93%
“…Lakes that are biologically invaded become more similar in species composition. , Invasion of exotic macrophytes has a strong detrimental impact on the abundance and diversity of the resident macrophytes, with common species becoming more widespread and rare species becoming rarer. , A previous study showed invasion of A. philoxeroides significantly reduced the number of species and seedling density in the soil seed bank of the reed community .…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Ramsar Convention has proposed the de nitions of urban and periurban wetlands based on the urbanperiurban gradient (Ramsar 2008). However, little is known about how the impact of invasive alien macrophytes on wetland soil including carbon pool, fertility, stoichiometry and microbial diversity, assemblage, structure and function along the urban-periurban gradient (Tasker et al 2022). In the present study, the impact of the nuisance invasive macrophyte, A. philoxeroides on wetland soil was studied in two river wetlands with different urbanization contexts.…”
Section: Introductionmentioning
confidence: 97%